The association between MICA/MICB polymorphism and respiratory syncytial virus infection in children. (18th September 2017) - Luo, Q.; Guo, X.; Peng, S.; Luo, W.; Tian, F.; Yu, P.; Zou, Y.
Summary: MICA/MICB gene polymorphisms are related to several cancers and infectious diseases, but there are no reports on the association between MICA/MICB gene polymorphisms and respiratory syncytial virus (RSV) infection. To clarify the association between MICA/MICB gene polymorphisms and infection of RSV in children, we collected fresh blood samples from paediatric patients with and without pneumonia after RSV infection. The MICA/MICB alleles were characterized by PCR sequence‐specific primers (PCR‐SSP) and PCR sequence‐based genotyping (PCR‐SBT), and then, the frequency of the MICA/MICB alleles and haplotypes was calculated. The results showed that the frequencies of MICA*002:01 and MICA‐A9 in RSV‐infected patients were significantly lower than in controls (9% vs. 20%, pc  = 0.04). The allele frequency of MICA*002:01 in pneumonia patients (8%) and nonpneumonia patients (9%) was significantly lower than in controls (20%, pc =  0.02). MICA*002:01‐MICB*008 (Δrel = 0.616), MICA*009‐MICB*016 (Δrel = 0.506), and MICA*045‐MICB*014 (Δrel = 0.700) showed linkage disequilibrium in patients infected with RSV. The haplotype frequency of MICA*002:01‐MICB*005:02 in RSV‐infected patients was significantly lower than in controls (10% vs. 16%, pc =  0.033). In conclusion, allele MICA*002:01/A9 and haplotype MICA*002:01‐MICB*005:02 were negatively associated with RSV respiratory tract infections.